UM VERGER, DOIS OLHARES: a construção da africanidade brasileira por um estrangeiro - Castro, Mauricio; Santos, Myrian (Caderno CRH, 2016)
As reflexões sobre o olhar estrangeiro têm sido frequentes nas últimas décadas, principalmente a partir da crítica à formação de um imaginário repleto de exotismo e sensualidade associado aos trópicos. Não é, portanto, exagero afirmar que o problema das representações, usos e abusos da imagem dos afrodescendentes no Brasil, ao longo dos séculos, permanece como foco importante para se entender a história das relações raciais no país. Nem sempre, contudo, procura-se o exótico nos trópicos. Este artigo procura analisar o impacto do olhar de Pierre Verger sobre a construção do legado africano no Brasil. Palavras-chave: Pierre Verger. Afrodescendentes. Relações raciais. ONE VERGER, TWO LOOKS: the construction of Brazilian africanity by a foreigner Maurício Barros de Castro Myrian Sepúlveda dos Santos Over the last decades a reflection upon the foreign look has become frequent, mainly from the point of view of critics to the creation of an imaginary filled with exoticism and sensuality associated to the tropics. So it is not an exaggeration to state that the problems with the representations, uses and overuses of the image of Brazilian afro-descendants throughout the centuries is still an important focus for understanding the history of racial relations in the country. However, it is not always that the exotic is sought in the tropics. This article analyzes the impact of the look of Pierre Verger on the construction of the African legacy in Brazil. Keywords: Pierre Verger. Afro-descendants. Racial relationships. UN PIERRE VERGER, DEUX REGARDS: la construction de l’africanité brésilienne par un étranger Maurício Barros de Castro Myrian Sepúlveda dos Santos Les réflexions faites sur le regard étranger ont été fréquentes au cours des dernières décennies, surtout si l’on prend en considération les critiques sur la formation d’un imaginaire rempli d’exotisme et de sensualité associé aux tropiques. Il n’est donc pas exagéré de dire que le problème des représentations, de l’utilisation et des abus faits de l’image des descendants africains au Brésil, tout au long des siècles, constitue toujours un élément important pour la compréhension de l’histoire des relations raciales dans le pays. On n’est cependant pas toujours à la recherche de l’exotisme sous les tropiques. Cet article essaie d’analyser l’impact du regard de Pierre Verger sur la construction de l’héritage africain au Brésil. Mots-clés: Pierre Verger. Ascendance/Descendance africaine. Relations raciales. <small style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: #ffffff;"> <br style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: #ffffff;" /> <br style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: #ffffff;" /> <small style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: #ffffff;">